UPAYA INDONESIA DALAM MELINDUNGI PEKERJA MIGRAN INDONESIA PADA SEKTOR INFORMAL DI TAIWAN TAHUN 2018 - 2020 - Nabilla Ramadhanty, (2022)
This study aims to describe the efforts by the Indonesian government to solve the problems of Indonesian Migrant Workers in the informal sector in Taiwan by optimizing their protection by using migration theory and protection diplomacy. It because there are frequent violations of the rights of Indonesian Migrant Workers in the informal sector in Taiwan such as unpaid wages, long working hours, and different types of work from the work agreement. The method used in this research is descriptive qualitative by using primary data sources through interviews with several informants and secondary data through various journals, books, articles etc. The final result of this study shows that the Indonesian government's efforts in 2018-2020 in protecting the informal Indonesian Migrant Workers sector are carried out through four stages, namely prevention, early detection, problem solving and evaluation. Although the efforts made have not completely eliminated the violation of the rights of Indonesian Migrant Workers in Taiwan, it is proven by this that Indonesia has carried out its obligations as a country to protect its citizens.